Manajemen Ibadah Haji Di Kantor Wilayah Kementerian Agama Provinsi Sulawesi Utara - Mangkuto, Rouldy R; Rares, Joyce; Dengo, Salmin (Sam Ratulangi University, 2016)
Abstract: the Hajj is mandatory practice for Muslims who are able to do once ina lifetime. Implementation of the Hajj in Makkah Al Mukarramah housed (Saudi Arabia)on the10th Dzulhijjah every year. Organize and restructure the Organization of theHajj is indeed not an easy job andonce so it can satisfy all parties. Methodology the study used qualitative method and become objects in thisresearch is the Managerof Hajj in the Regional Office of the Ministry of religion of North Sulawesiprovince and pilgrims period 2013 – 2015 and other Islamic organizations. Data collection is carried out bymeans of interviews to 15 informants consist of four staff in theOfficeof Kemenag Prov. Flammable (SISKOHAT), 2 representatives of BPS-BPIH, 6 peoplepilgrims by 2013 –2015, 3 people from religious figures/community. As for the goalin this research that the management of theOrganization of the Hajj in North Sulawesi province were still low so that the role of management inorganizing the Hajj should be further enhanced, as well as the understanding of the people aboutthe management and service of pilgrimage in some things to be fixed. From this research it can be concludedthat pull in the management of the Organization of the pilgrimage in North Sulawesi wasstill low. Recommended socialisation, improved infrastructure and increasing the professionalism of theofficers work.Keywords: Management Of Organizing The Pilgrimage.